Arteriovenous malformations of the colon: A report of two cases and review of the literature - Ghodratollah Maddah; Abbas Abdollahi; Omid Rouhbakhshfar; Shirin Taraz Jamshidi; Masoumeh Hassanpour (Babol University of Medical Sciences, 2017)
Background: Arteriovenous malformations are one of the most common vascular disorders of the colon. Vascular disorders present as painless, high-volume rectal bleeding. Case Presentation: This study elucidates two rare cases of vascular disorders that are diagnosed as angiodysplasia of the left colon and cavernous hemangioma of the colon and rectum.  The chief complaint in two patients was rectorrhagia. The patients who were diagnosed of ulcerative colitis were treated with sulfadiazine and prednisone. Due to continuous bleeding, the patients were referred to the surgery department for operation. The patients underwent total proctocolectomy. Conclusion: We discuss the faults in the diagnosis and management of vascular disorders of the intestine.